Kelayakan Body Scrub Kopi dan Beras untuk Kecerahan Kulit - Luthfita, Shalsabilla; Dewi, Siska Miga; Ningsih, Ratih Ayu Setia (Jurnal Tata Rias, 2023)
The skin describes one of the organs that has an important role, therefore it is always good to treat and maintain healthy skin. Types of skin care activities according to each person's skin type. Body scrub is a body treatment using scrubs, there are several types of body scrubs such as coffee and rice. The type of research being conducted was a quantitative descriptive study which aimed to find out how to make a coffee and rice body scrub for skin lightening. This study was used to test the content of Vitamin B1 contained in coffee and rice body scrubs and to determine the quality of the texture, aroma, stickiness, and level of preference of the panelists. Based on the results of research that has been done about the feasibility of coffee and rice body scrubs, they are suitable for body care for skin brightness.